Bone mineral density, dietary habits, and menstrual status in young gymnasts - Horea, J. H.; Berning, J. (Medicine & Science in Sports & Exercise, 1998)
This study examined bone mineral density, menstrual status, and dietary habits of highly trained female gymnasts (N = 13) and normally active matched controls (matched for age, height, and weight; N = 13). There were no significant differences in mean bone mass density for the total body, spine, or pelvis but gymnasts had greater density in the arms and legs. There were no differences in dietary calcium, protein, menarche (13.15 years), menstrual status, or incidence of dieting. Implication. Female gymnasts are structurally normal except for great bone density in the body sites that bear extreme forces, that is, the legs and arms.